1980
DOI: 10.1038/284360a0
|View full text |Cite
|
Sign up to set email alerts
|

Low intracellular pH and chemical agents slow inactivation gating in sodium channels of muscle

Abstract: Excitation of nerve or muscle requires an orderly opening and closing of molecular pores, the ionic channels, in the plasma membrane. During the action potential, Na channels are opened (activated) by the advancing wave of depolarisation, contributing a pulse of inward sodium current, and then are closed again (inactivated) by the continued depolarisation. As one approach both to obtaining molecular information on the Na channel and towards further defining the recently discovered kinetic interactions of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 18 publications
5
47
0
1
Order By: Relevance
“…Externally and internally applied TNBS acts on the sodium channel located on the plasma membrane of the frog muscle fibre in completely different ways. It accelerates inactivation when applied extracellularly (Cahalan & Pappone, 1981), while it blocks inactivation when applied intracellularly (Nonner, Spalding & Hille, 1980). TNBS almost certainly acts, at least in the first stage of the reaction, on the external surface of the presynaptic membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Externally and internally applied TNBS acts on the sodium channel located on the plasma membrane of the frog muscle fibre in completely different ways. It accelerates inactivation when applied extracellularly (Cahalan & Pappone, 1981), while it blocks inactivation when applied intracellularly (Nonner, Spalding & Hille, 1980). TNBS almost certainly acts, at least in the first stage of the reaction, on the external surface of the presynaptic membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage alone, however, only indicates the presence, and not the functional importance, of these residues . Subsequent experiments with lysineand arginine-modifying reagents and with agents that mimic peptides containing arginine Kirsch et al, 1980;Lo and Shrager, 1982;Nonner et al, 1980) have demonstrated that an arginine residue was probably present and was an integral part of the inactivation mechanism.…”
Section: Comparison With Single Myelinated Fibersmentioning
confidence: 99%
“…Intracellular acidification delays inactivation of the Na+ current in frog skeletal muscle (Nonner, Spalding & Hille, 1980). In cardiac muscle, Ca2+ currents are inhibited by lowering pHi (Vogel & Sperelakis, 1977;Irisawa & Sato, 1986;Kaibara & Kameyama, 1988).…”
Section: Introductionmentioning
confidence: 99%